Left Atrial Appendage Closure Devices. Issue 8 (January 2014) - Romero, Jorge; Perez, Irving E.; Krumerman, Andrew; Garcia, Mario J.; Lucariello, Richard J.
Atrial fibrillation (AF) increases the risk for thromboembolic stroke five-fold. The left atrial appendage (LAA) has been shown to be the main source of thrombus formation in the majority of strokes associated with AF. Oral anticoagulation with warfarin and novel anticoagulants remains the standard of care; however, it has several limitations, including bleeding and poor compliance. Occlusion of the LAA has been shown to be an alternative therapeutic approach to drug therapy. The purpose of this article is to review the different techniques and devices that have emerged for the purpose of occluding this structure, with a particular emphasis on the efficacy and safety studies published to date in the medical literature.